A PRIEST IN JESTER’S CLOTHING - Hearsey, Paddy (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1971)
Donald F. Theall. THE MEDIUM IS THE REAR VIEW MIRROR - UNDERSTANDING McLUHAN. Montreal McGill-Queen’s University Press, 1971. 261 pp. 8.75.